Carbon nanotube hard carbon composite material and preparation method and application thereof

By covering the hard carbon carbon coating of carbon nanotubes on the surface of the graphite material, the problems of limited capacity, poor stability and poor rate performance of traditional graphite negative electrode materials are solved, and the high capacity, excellent cycling performance and fast charging and discharge capability of carbon nanotube hard carbon composite materials are achieved.

CN119683615AInactive Publication Date: 2025-03-25FUJIAN SHANSHAN TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411844302.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional graphite negative electrode materials have problems such as limited capacity, poor layered structure stability, large irreversible capacity resulting from electrolyte decomposition and poor rate performance, which limits their application in high-performance and high-power batteries.

Method used

By coating the hard carbon carbon nanotube coating on the surface of the graphite material, the coating ratio of carbon nanotubes and hard carbon is adjusted, and carbon nanotube hard carbon composite materials are prepared. The method includes preoxidation and carbonization treatment steps to form a stable hard carbon structure and carbon nanotube network.

Benefits of technology

It significantly improves the initial discharge capacity, Coulomb efficiency, rate performance and cycle stability of carbon nanotube hard carbon composite materials, realizes fast charging and discharge and high battery capacity, and extends the energy storage life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683615A_ABST
    Figure CN119683615A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanotube hard carbon composite material as well as a preparation method and application thereof. The preparation method of the carbon nanotube hard carbon composite material comprises the following steps: carrying out pre-oxidation treatment on a mixture A, and then carrying out carbonization treatment; the mixture A comprises graphite particles, single-walled carbon nanotubes, polyacrylonitrile and a solvent. According to the carbon nanotube hard carbon composite material disclosed by the invention, the surface of the graphite material is coated with the carbon nanotube hard carbon coating, and the ratio of the carbon nanotube to the hard carbon coating is adjusted, so that the initial discharge capacity, the first coulombic efficiency, the rate capability and the cycling stability of a battery prepared from the carbon nanotube hard carbon composite material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon nanotube hard carbon composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in mobile communications, information technology, consumer electronics, and mobile vehicles due to their excellent energy storage properties. With the advancement of technology and the increase in application needs, higher requirements are placed on lithium-ion batteries, including higher capacity, better rate performance, and longer service life. Among all the components of lithium-ion batteries, electrode materials are the key factors that restrict the performance of lithium-ion batteries. Among them, the negative electrode material, as an important component of lithium-ion batteries, has an important influence on the electrochemical properties of lithium-ion batteries.

[0003] Among the negative electrode materials of lithium-ion batteries, carbon materials have become the preferred materials due to their advantages such as low electrode potential, high cycle efficiency, long cycle life and good safety performance. At present, graphite is a common carbon negative electrode material with a good layered structure suitable for lithium ion embedding and de-embedding, thus showing advantages such as high conductivity and high reversible specific capacity, becoming a widely used negative electrode material.

[0004] However, traditional graphite negative electrode materials still have some shortcomings, which seriously limit their application. First, the theoretical capacity of graphite negative electrode is only 372mAh / g, which is far from meeting the requirements of high-performance lithium-ion batteries; second, the layered structure of graphite negative electrode is easy to collapse during long-term charge and discharge cycles, resulting in a significant decrease in specific capacity and a significant shortening of energy storage life; third, during the first charge and discharge process, the graphite negative electrode will cause a large irreversible capacity loss due to electrolyte decomposition. These defects have greatly limited the application of graphite negative electrode materials in high-performance lithium-ion batteries. In addition, the interlayer spacing of graphite is small, and lithium ions can only be embedded from the end face of the material, which increases the diffusion resistance of lithium ions, further limiting the rate performance of graphite negative electrode, and limiting its application in high-power batteries.

[0005] Therefore, the rate performance of layered graphite anode is poor, which limits its application in high-power batteries. Finding graphite anode materials with high performance, high capacity, high stability and long cycle life is an important issue that needs to be solved urgently. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects of the conventional graphite negative electrode materials in the prior art, such as limited capacity, poor layered structure stability, large irreversible capacity due to electrolyte decomposition, and poor rate performance, which limit their application in high-performance and high-power batteries, and to provide a carbon nanotube hard carbon composite material and its preparation method and application. The carbon nanotube hard carbon composite material of the present invention significantly improves the initial discharge capacity, coulomb efficiency, rate performance and cycle stability of the battery made of the carbon nanotube hard carbon composite material by coating the carbon nanotube hard carbon coating on the surface of the graphite material and adjusting the coating ratio of the carbon nanotube and the hard carbon.

[0007] The present invention solves the above technical problems through the following technical solutions:

[0008] The present invention provides a method for preparing a carbon nanotube hard carbon composite material, which comprises the following steps:

[0009] Pre-oxidation treatment of the mixed material A and then carbonization treatment;

[0010] The mixed material A comprises graphite particles, single-walled carbon nanotubes, polyacrylonitrile and a solvent.

[0011] In this scheme, the presence of single-walled carbon nanotubes can enhance the conductivity and crystallinity of polyacrylonitrile. The molecular chains of single-walled carbon nanotubes and polyacrylonitrile can be entangled with each other to form a strong physical cross-linking structure, which helps to improve the thermal stability and mechanical stability of the composite material.

[0012] Preferably, the molecular weight of the polyacrylonitrile is 100,000-200,000 g / mol, for example 150,000 g / mol.

[0013] In this scheme, the higher molecular weight of polyacrylonitrile helps to form a stable hard carbon structure, providing strong mechanical strength and electrical conductivity, thereby enhancing the conductivity and structural stability of the composite material.

[0014] Preferably, the mass ratio of the polyacrylonitrile to the single-walled carbon nanotube is 1:(0.001-0.003), for example, 1:0.002.

[0015] In this scheme, single-walled carbon nanotubes are easily aggregated in polyacrylonitrile, resulting in the uniformity and performance of the composite material being affected. Using different coating amounts mixed with graphite will produce different effects. The appropriate coating ratio will amplify the synergistic effect of polyacrylonitrile and single-walled carbon nanotubes. Too small or excessive coating amounts will prevent the mixed solution A from being evenly dispersed on the surface of graphite particles. The mass ratio of polyacrylonitrile to single-walled carbon nanotubes in this scheme helps to improve the uniformity of the carbon nanotube hard carbon composite material and enhance the conductivity and structural stability of the composite material.

[0016] Preferably, the diameter of the graphite particles is 10-20 μm, more preferably 15 μm.

[0017] Preferably, the mass ratio of the polyacrylonitrile to the graphite particles is 1:(6-13), for example, 1:6.25, 1:8.3 or 1:12.5.

[0018] Preferably, the diameter of the single-walled carbon nanotube is 1-10 nm, more preferably 1-5 nm, such as 3 nm.

[0019] Preferably, the length of the single-walled carbon nanotube is greater than 2 μm, more preferably greater than 5 μm, such as 6 μm.

[0020] Preferably, the solvent is a combination of one or more of dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran and water, such as N,N-dimethylformamide.

[0021] In this scheme, single-walled carbon nanotubes have high conductivity and good mechanical reinforcement effect. When the volume of the electrode changes, it can maintain structural stability and prevent collapse through its mechanical reinforcement effect.

[0022] Preferably, the preparation method of the mixed material A is to first mix the slurry containing the single-walled carbon nanotubes with the solution containing the polyacrylonitrile, heat and stir to obtain a mixed solution B, and then mix the mixed solution B with the graphite particles.

[0023] More preferably, the slurry of single-walled carbon nanotubes is a conductive carbon slurry containing single-walled carbon nanotubes and sodium carboxymethyl cellulose.

[0024] More preferably, the single-walled carbon nanotube slurry is a conductive carbon slurry containing 0.4% single-walled carbon nanotubes and sodium carboxymethyl cellulose, where % refers to the mass fraction of the single-walled carbon nanotubes to the total mass of the conductive carbon slurry.

[0025] In this scheme, adding a small amount of single-walled carbon nanotubes can reduce the battery internal resistance (DCR). Even after multiple battery charge and discharge cycles and battery storage cycles, a stable single-walled carbon nanotube network can still be maintained in the negative electrode material, thereby keeping the internal resistance at a low level after high-temperature storage and cycling, reducing the risk of battery fire.

[0026] More preferably, the device used for the heating and stirring is a magnetic stirrer.

[0027] More preferably, the heating and stirring rotation speed is 600-1200 rpm, for example 800 rpm.

[0028] More preferably, the temperature of the heating and stirring is 50-70°C, such as 60°C.

[0029] More preferably, the heating and stirring time is 5-7 h, such as 6 h.

[0030] In this solution, the heating and stirring can ensure the full dissolution and uniform mixing of polyacrylonitrile and single-walled carbon nanotubes, thereby improving the uniformity and performance stability of the composite material.

[0031] Preferably, the graphite particles are mixed with the mixed solution A by stirring.

[0032] Further preferably, during the process of mixing the mixed solution B with the graphite particles, the device used for stirring is a stirrer.

[0033] Further preferably, during the process of mixing the mixed solution B with the graphite particles, the stirring speed is 600-1200 rpm, 800 rpm.

[0034] Further preferably, during the process of mixing the mixed solution B with the graphite particles, the stirring time is 3-9 hours, for example, 5 hours.

[0035] In this solution, the graphite particles and the mixed solution A are mixed by stirring so that the subsequently generated carbon nanotube hard carbon coating is evenly distributed and wrapped on the surface of the graphite particles.

[0036] More preferably, the solution containing the polyacrylonitrile is prepared by mixing polyacrylonitrile with a solvent, and heating and stirring.

[0037] More preferably, the solvent of the polyacrylonitrile solution is dimethyl sulfoxide, N,N-dimethylformamide or tetrahydrofuran, such as N,N-dimethylformamide.

[0038] More preferably, the equipment used for the heating and stirring is a magnetic stirrer.

[0039] More preferably, the stirring speed of the heating stirring is 600-1200 rpm, for example 800 rpm.

[0040] More preferably, the temperature of the heating and stirring is 50-70°C, such as 60°C.

[0041] More preferably, the heating and stirring time is 8-14 h, such as 12 h.

[0042] In the present invention, preferably, the pre-oxidation treatment satisfies one or more of the following conditions:

[0043] (1) The pre-oxidation treatment device is a tubular furnace;

[0044] (2) The end temperature of the pre-oxidation treatment is 150-200°C, for example 180°C;

[0045] (3) the heating rate from room temperature to the end temperature of the pre-oxidation treatment is 2-5°C / min, for example 3°C / min;

[0046] (4) After the pre-oxidation treatment reaches the end temperature, the holding time is 0.5-2h, for example 1h;

[0047] (5) The pre-oxidation treatment is carried out in air.

[0048] In this scheme, a reasonable pre-oxidation treatment holding time is helpful for fully oxidizing polyacrylonitrile and removing most of the organic components, thus providing appropriate conditions for the formation of hard carbon.

[0049] In the present invention, preferably, the carbonization treatment satisfies one or more of the following conditions:

[0050] (1) The carbonization treatment device is a tubular furnace;

[0051] (2) The end temperature of the carbonization treatment is 900-1300° C., for example, 1100° C.;

[0052] (3) the heating rate from the end temperature of the pre-oxidation treatment to the end temperature of the carbonization treatment is 8-12°C / min, for example, 10°C / min;

[0053] (4) After the carbonization treatment reaches the end temperature, the heat preservation time is 1-3 hours, for example, 2 hours;

[0054] (5) The carbonization treatment is carried out in an inert atmosphere, and the inert atmosphere is preferably nitrogen.

[0055] In the present invention, preferably, the carbonization treatment further includes the steps of cleaning and drying.

[0056] More preferably, the cleaning solution is 70% alcohol.

[0057] More preferably, the drying temperature is 50-70°C, for example 60°C.

[0058] The present invention provides a carbon nanotube hard carbon composite material prepared by the method for preparing the carbon nanotube hard carbon composite material as described above.

[0059] The present invention provides an application of the carbon nanotube hard carbon composite material as described above as a negative electrode material in a lithium ion battery.

[0060] The positive and progressive effects of the present invention are:

[0061] (1) Rapid charging and discharging and high battery capacity can be achieved. In the present invention, the carbon nanotube hard carbon coating is evenly distributed and wrapped on the surface of the graphite particles. The single-walled carbon nanotube has excellent conductivity and good mechanical reinforcement effect. When the volume of the electrode changes, it can maintain structural stability and prevent collapse through its mechanical reinforcement effect, thereby achieving rapid charging and discharging and high battery capacity.

[0062] (2) Excellent capacity and cycle performance. The carbon nanotube hard carbon coating of the present invention significantly improves the diffusion capacity of lithium ions, further improving the high-current charge and discharge performance of graphite materials. The hard carbon layer can also form a protective film on the graphite surface, reduce irreversible side reactions, inhibit the formation of SEI film, reduce the specific surface area of ​​graphite, and avoid the capacity drop caused by solvent co-insertion. At the same time, the hard carbon layer restricts and buffers the volume expansion of graphite, increasing the stability of the cycle. These characteristics effectively improve the capacity and cycle performance of batteries made from carbon nanotube hard carbon composite materials, and improve the overall stability and long-term effectiveness of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 (a) XRD spectra of samples of Examples 1-3 and Comparative Examples 1-2 and (b) local enlarged spectra.

[0064] Figure 2 The Raman spectra of the samples of Examples 1-3 and Comparative Examples 1-2 are shown.

[0065] Figure 3 It is the first charge and discharge capacity diagram of the samples of Examples 1-3 and Comparative Examples 1-2.

[0066] Figure 4 The discharge capacity diagram of the samples of Examples 1-3 and Comparative Examples 1-2 at different rates.

[0067] Figure 5 It is the cycle performance diagram of the samples of Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0068] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0069] In the following examples, the molecular weight of polyacrylonitrile is 150,000 g / mol and is purchased from Mairui Biochemical Technology Co., Ltd.

[0070] In the following examples, the purity of N,N-dimethylformamide was >99.9%, and it was purchased from Merrill Biochemical Technology Co., Ltd.

[0071] In the following examples, the single-walled carbon nanotube content in the single-walled carbon nanotube slurry is 0.4%, and it is purchased from Shenyang Huijing Nanotechnology Co., Ltd. The single-walled carbon nanotube has a diameter of 3 nm and a length of 6 μm.

[0072] In the following examples, the diameter of the artificial graphite secondary particles is 15 μm and is sourced from Shanghai Shanshan Technology Co., Ltd.

[0073] In the following examples, the magnetic stirrer was purchased from IKA, model number C-MAG-HS-10.

[0074] In the following examples, the agitator was purchased from IKA, model IKA-MICROST AR 200.

[0075] In the following examples, the tubular furnace was purchased from Hefei Kejing Material Technology Co., Ltd., model number is GSL-1400X.

[0076] Example 1

[0077] 1. Take 6 g of polyacrylonitrile (150,000 g / mol) and dissolve it in DMF with a mass 4 times that of polyacrylonitrile.

[0078] 2. Use a magnetic stirrer to heat and stir at 60°C and 800 rpm for 12 hours to obtain a solution containing polyacrylonitrile.

[0079] 3. Take a slurry of single-walled carbon nanotubes with a mass of 0.5 times that of polyacrylonitrile, add the above polyacrylonitrile solution thereto, and heat and stir at 60°C and 800 rpm using a magnetic stirrer for 6 hours to obtain a mixed solution B.

[0080] 4. Take artificial graphite secondary particles with a mass 12.5 times that of polyacrylonitrile and add the above mixed solution B thereto.

[0081] 5. Use a stirrer to stir at 800 rpm for 5 hours to obtain mixed material A.

[0082] 6. Use a tubular furnace to heat the mixture A in air at 3°C / min to 180°C, keep it warm for 1 hour, then introduce nitrogen and heat it to 1100°C at 10°C / min, keep it at 1100°C for 2 hours, and then cool it naturally to room temperature.

[0083] 7. Take out the carbonized sample and clean it with 70% alcohol solution.

[0084] 8. After cleaning, the final sample was dried in a vacuum oven at 60°C and named HCTG-1.

[0085] Example 2

[0086] 1. Take 6 g of polyacrylonitrile (150,000 g / mol) and dissolve it in DMF with a mass 4 times that of polyacrylonitrile.

[0087] 2. Use a magnetic stirrer to heat and stir at 60°C and 800 rpm for 12 hours to obtain a solution containing polyacrylonitrile.

[0088] 3. Take a single-walled carbon nanotube slurry with a mass of 0.5 times that of polyacrylonitrile, add the above polyacrylonitrile solution thereto, and heat and stir at 60°C and 800 rpm using a magnetic stirrer for 6 hours to obtain a mixed solution B.

[0089] 4. Take artificial graphite secondary particles with a mass 8.3 times that of polyacrylonitrile and add the above mixed solution B thereto.

[0090] 5. Use a stirrer to stir at 800 rpm for 5 hours to obtain mixed material A.

[0091] 6. Use a tubular furnace to heat the mixture A in air at 3°C / min to 180°C, keep it warm for 1 hour, then introduce nitrogen and heat it to 1100°C at 10°C / min, keep it at 1100°C for 2 hours, and then cool it naturally to room temperature.

[0092] 7. Take out the carbonized sample and clean it with 70% alcohol solution.

[0093] 8. After cleaning, the final sample was dried in a vacuum oven at 60°C and named HCTG-2.

[0094] Example 3

[0095] 1. Take 6 g of polyacrylonitrile (150,000 g / mol) and dissolve it in DMF with a mass 4 times that of polyacrylonitrile.

[0096] 2. Use a magnetic stirrer to heat and stir at 60°C and 800 rpm for 12 hours to obtain a solution containing polyacrylonitrile.

[0097] 3. Take a single-walled carbon nanotube slurry with a mass of 0.5 times that of polyacrylonitrile, add the above polyacrylonitrile solution thereto, and heat and stir at 60°C and 800 rpm using a magnetic stirrer for 6 hours to obtain a mixed solution B.

[0098] 4. Take artificial graphite secondary particles with a mass 6.25 times that of polyacrylonitrile and add the above mixed solution B thereto.

[0099] 5. Use a stirrer to stir at 800 rpm for 5 hours to obtain mixed material A.

[0100] 6. Use a tubular furnace to heat the mixture A in air at 3°C / min to 180°C, keep it warm for 1 hour, then introduce nitrogen and heat it to 1100°C at 10°C / min, keep it at 1100°C for 2 hours, and then cool it naturally to room temperature.

[0101] 7. Take out the carbonized sample and clean it with 70% alcohol solution.

[0102] 8. After cleaning, the final sample was dried in a vacuum oven at 60°C and named HCTG-3.

[0103] Comparative Example 1

[0104] 1. Take 6 g of polyacrylonitrile (150,000 g / mol) and dissolve it in DMF which is 4 times the mass of polyacrylonitrile.

[0105] 2. Use a magnetic stirrer to heat and stir at 60°C and 800 rpm for 12 hours to obtain a solution containing polyacrylonitrile.

[0106] 3. Take artificial graphite secondary particles with a mass 12.5 times that of polyacrylonitrile and add the above polyacrylonitrile solution thereto.

[0107] 4. Use a stirrer to stir at a constant speed for 5 hours to obtain a mixture.

[0108] 5. Use a tubular furnace to heat the mixture in air to 180°C at 3°C / min, keep it warm for 1 hour, then introduce nitrogen and heat it to 1100°C at 10°C / min, keep it at 1100°C for 2 hours, and then cool it naturally to room temperature.

[0109] 6. Take out the carbonized sample and clean it with 70% alcohol solution.

[0110] 7. After cleaning, the final sample was obtained by drying in a vacuum oven at 60°C and named HCG-1.

[0111] Comparative Example 2

[0112] The secondary particle artificial graphite without any treatment is named AG.

[0113] Effect Example

[0114] (1) XRD test

[0115] XRD tests were performed on HCTG-1, HCTG-2, HCTG-3, HCG-1 and AG. Figure 1 (a) shows the X-ray diffraction patterns (XRD) of various examples and comparative examples, Figure 1(b) is a partial enlarged image. It can be seen from the image that only the graphite phase can be detected by X-ray diffraction. This is because the content of hard carbon is small and the crystallinity is poor, so their characteristic peaks cannot be detected in the XRD spectrum. Figure 1 It can be found in (b) that as the content of polyacrylonitrile in the surface coating increases from HCTG-1 to HCTG-2 and then to HCTG-3, the diffraction peak intensity corresponding to the graphite (002) crystal plane decreases significantly. This is because the introduction of the amorphous layer weakens the crystal orientation of graphite in the XRD spectrum.

[0116] (2) Raman spectroscopy analysis

[0117] Figure 2 The Raman spectra of HCTG-1, HCTG-2, HCTG-3, HCG-1 and AG are shown. The Raman spectra of HCTG-1, HCTG-2, HCTG-3 and HCG-1 are at 1350 cm -1 and 1580cm -1 Raman peaks appear at 1350 cm -1 The D band corresponds to amorphous carbon, with a peak at 1580 cm -1 The G band corresponds to graphite crystalline carbon. Since AG does not contain amorphous carbon, it only occurs at 1580 cm -1 There is a sharp G peak near 1350cm -1 An additional strong D peak is shown at the location, which proves that the carbon nanotube hard carbon coating in the samples of Examples 1-3 is successfully prepared, and the intensity of the D peak is also enhanced with the increase of the coated carbon content.

[0118] (3) Initial discharge capacity and first coulombic efficiency test

[0119] 85 wt% of the products of Examples 1-3 and Comparative Examples 1-2, 5 wt% of conductive carbon black and 10 wt% of polyvinylidene fluoride (PVDF) binder were mixed into slurries respectively. The slurries used N-methyl-2-pyrrolidone (NMP) as a solvent.

[0120] Assembly process: The fully mixed slurry was coated on the current collector (copper foil) and then vacuum dried at 120 °C for 12 h. The diameter of the punched electrode was 14 mm and had a conductivity of about 3.3 mg cm -2 Loading density of active materials. Metallic lithium (Li) was used as the counter electrode / reference electrode, and 1.2 M lithium hexafluorophosphate (LiPF6) and ethyl methyl carbonate (3:7 wt%) were used as the electrolyte. The half-cell was assembled into a button-type lithium battery in an argon-filled glove box.

[0121] like Figure 3As shown, the initial discharge capacities of HCTG-1, HCTG-2, HCTG-3, HCG-1 and AG are 427.4, 408.6, 419.4, 431.6 and 396.1 mAh / g, respectively, and their first coulombic efficiencies (ICE) are 83.4%, 86.6%, 84.4%, 82.3% and 89.4%, respectively. It can be seen that the hard carbon coating layer HCTG-1 with single-walled carbon nanotubes added in Example 1 has a higher initial efficiency than the simple hard carbon coating layer HCG-1 in Comparative Example 1, indicating that the performance of the battery can be effectively improved by adding single-walled carbon nanotubes. In the example, HCTG-2 has the highest capacity and the highest coulombic efficiency, indicating that the appropriate hard carbon and carbon nanotube content coating layer is beneficial to improving the capacity and efficiency of the material. Too high a content will affect the embedding of lithium ions, resulting in a decrease in capacity and efficiency.

[0122] (4) Rate performance test

[0123] Figure 4 The rate performance after assembly and charging using Examples 1-3 and Comparative Examples 1-2 is shown. The rate performance is tested using 0.2C, 0.5C, 1C, 2C, 3C and 5C. The reversible specific capacities of AG are 354.8mAh / g, 294.7mAh / g, 220.6mAh / g, 139.9mAh / g, 60.2mAh / g and 18.2mAh / g, respectively. After coating with a hard carbon coating, the rate performance of HCG-1 is significantly improved compared to AG. After adding single-walled carbon nanotubes, the rate performance of HCTG-1 is further improved compared to HCG-1. HCTG-2 shows the best rate performance after increasing the coating ratio of the composite carbon material. The details are shown in Table 1 below. The carbon nanotube hard carbon coating in HCTG-1, HCTG-2, and HCTG-3 makes the carbon on the surface of the material more disordered and provides additional lithium embedding channels, which is beneficial for large current charging and discharging. However, excessive carbon coating will also increase resistance to lithium ion embedding and affect rate performance.

[0124] Table 1

[0125]

[0126] (5) Cyclic performance test

[0127] Figure 5The cycle performance of each embodiment and comparative example after assembly and power-on is shown. HCTG-2 has the best cycle performance at a larger current density. After 150 cycles at a rate of 1C, it still maintains a reversible specific capacity of 276.3mAh / g, which is much higher than AG's 142.4mAh / g. HCTG-2 calculated that the capacity retention rate after 150 cycles at a current density of 1C is as high as 93.8%. It is proved that artificial graphite using polyacrylonitrile as hard carbon and carbon nanotube composite coating has excellent cycle performance.

Claims

1. A method for preparing a carbon nanotube hard carbon composite material, characterized in that: It includes the following steps: Pre-oxidation treatment of the mixed material A and then carbonization treatment; The mixed material A comprises graphite particles, single-walled carbon nanotubes, polyacrylonitrile and a solvent.

2. The method for preparing the carbon nanotube hard carbon composite material according to claim 1, characterized in that: The method for preparing the carbon nanotube hard carbon composite material meets one or more of the following conditions: (1) The molecular weight of the polyacrylonitrile is 100,000-200,000 g / mol, for example, 150,000 g / mol; (2) The mass ratio of the polyacrylonitrile to the single-walled carbon nanotube is 1:(0.001-0.003), for example, 1:0.002; (3) The diameter of the graphite particles is 10-20 μm, preferably 15 μm; (4) The mass ratio of the polyacrylonitrile to the graphite particles is 1:(6-13), for example, 1:6.25, 1:8.3 or 1:12.5; (5) The diameter of the single-walled carbon nanotube is 1-10 nm, preferably 1-5 nm, for example 3 nm; (6) The length of the single-walled carbon nanotube is greater than 2 μm, preferably greater than 5 μm, for example 6 μm; (7) The solvent is a combination of one or more of dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran and water, such as N,N-dimethylformamide.

3. The method for preparing the carbon nanotube hard carbon composite material according to claim 1, characterized in that: The preparation method of the mixed material A is to first mix the slurry containing the single-walled carbon nanotubes with the solution containing the polyacrylonitrile, heat and stir to obtain a mixed solution B, and then mix the mixed solution B with the graphite particles; Preferably, the slurry of single-walled carbon nanotubes is a conductive carbon slurry containing single-walled carbon nanotubes and sodium carboxymethyl cellulose; More preferably, the single-walled carbon nanotube slurry is a conductive carbon slurry containing 0.4% single-walled carbon nanotubes and sodium carboxymethyl cellulose, where % refers to the mass fraction of the single-walled carbon nanotubes to the total mass of the conductive carbon slurry; Preferably, the device used for heating and stirring is a magnetic stirrer; Preferably, the speed of the heating and stirring is 600-1200 rpm, for example 800 rpm; Preferably, the temperature of the heating and stirring is 50-70°C, for example 60°C; Preferably, the heating and stirring time is 5-7h, for example 6h; Preferably, in the process of mixing the mixed solution B with the graphite particles, the stirring device used is a stirrer; Preferably, during the process of mixing the mixed solution B with the graphite particles, the stirring speed is 600-1200 rpm, 800 rpm; Preferably, during the process of mixing the mixed solution B with the graphite particles, the stirring time is 3-9 hours, for example, 5 hours.

4. The method for preparing the carbon nanotube hard carbon composite material according to claim 3, characterized in that: The method for preparing the solution containing the polyacrylonitrile is to mix polyacrylonitrile with a solvent, and heat and stir.

5. The method for preparing the carbon nanotube hard carbon composite material according to claim 4, characterized in that: The method for preparing the polyacrylonitrile solution satisfies one or more of the following conditions: (1) The solvent of the polyacrylonitrile solution is dimethyl sulfoxide, N,N-dimethylformamide or tetrahydrofuran, such as N,N-dimethylformamide; (2) The equipment used for heating and stirring is a magnetic stirrer; (3) The stirring speed of the heating stirring is 600-1200 rpm, for example 800 rpm; (4) The heating and stirring temperature is 50-70° C., for example 60° C.; (5) The heating and stirring time is 8-14 hours, for example 12 hours.

6. The method for preparing the carbon nanotube hard carbon composite material according to claim 1, characterized in that: The pre-oxidation treatment satisfies one or more of the following conditions: (1) The pre-oxidation treatment device is a tubular furnace; (2) The end temperature of the pre-oxidation treatment is 150-200°C, for example 180°C; (3) the heating rate from room temperature to the end temperature of the pre-oxidation treatment is 2-5°C / min, for example 3°C / min; (4) After the pre-oxidation treatment reaches the end temperature, the holding time is 0.5-2h, for example 1h; (5) The pre-oxidation treatment is carried out in air.

7. The method for preparing the carbon nanotube hard carbon composite material according to claim 1, characterized in that: The carbonization treatment satisfies one or more of the following conditions: (1) The carbonization treatment device is a tubular furnace; (2) The end temperature of the carbonization treatment is 900-1300° C., for example, 1100° C.; (3) the heating rate from the end temperature of the pre-oxidation treatment to the end temperature of the carbonization treatment is 8-12°C / min, for example, 10°C / min; (4) After the carbonization treatment reaches the end temperature, the heat preservation time is 1-3 hours, for example, 2 hours; (5) The carbonization treatment is carried out in an inert atmosphere, and the inert atmosphere is preferably nitrogen.

8. The method for preparing the carbon nanotube hard carbon composite material according to claim 1, characterized in that: The carbonization treatment also includes the steps of cleaning and drying; Preferably, the cleaning solution is 70% alcohol; Preferably, the drying temperature is 50-70°C, for example 60°C.

9. A carbon nanotube hard carbon composite material prepared by the method for preparing a carbon nanotube hard carbon composite material as described in any one of claims 1 to 8.

10. Use of the carbon nanotube hard carbon composite material as claimed in claim 9 as a negative electrode material in a lithium ion battery.

Citation Information

Patent Citations

  • Negative electrode slurry, negative electrode plate as well as preparation method and application thereof

    CN112054201A

  • Preparation method of graphite composite material with long service life and high power

    CN114094097A

  • Graphite composite material, preparation method thereof and lithium ion battery

    CN115084456A

  • Negative active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same

    KR1020130015967A